Digital transformation and user experience: A bibliometric analysis of academic research (2014–2024) - Safaa, TIGHAZRI; Ichraq, HAMMOU; Olaya, METWALLI; L’Houssaine, MOUNAIM (International Journal of Innovative Research and Scientific Studies, 2025)
This paper explores the articulation between digital transformation and user experience (UX) through a bibliometric and descriptive approach based on the Scopus database. The purpose of the study is to address the fragmented state of research in this area and to provide an integrated overview that clarifies its evolution and main directions. The study relies on a corpus of 236 articles published between 2014 and 2024 in the field of management and business research. Findings highlight a significant growth in publications from 2018 onwards, with an unprecedented peak in 2024. While pioneering journals such as Technological Forecasting and Social Change and Technology in Society remain dominant, the field is progressively diversifying across multiple outlets. Geographically, the United States, China, and the United Kingdom lead academic production, although emerging countries such as Malaysia, India, and Ukraine are increasingly visible. The analysis also reveals persistent fragmentation: collaborations between authors and institutions remain limited, and no central academic figure has yet emerged. Keyword co-occurrence mapping identifies core themes around technological innovation, digital services, sustainability, and inclusivity. The study concludes that research on digital transformation and UX is expanding rapidly, but remains structurally fragmented and lacks unifying scholarly leadership. By offering an integrated view of this evolving field, it contributes to consolidation of digital transformation and UX research while outlining key challenges and opportunities for future investigations. The practical implications lie in guiding researchers toward greater collaboration and thematic integration, while offering practitioners and policymakers insights into how digital transformation can be more effectively aligned with inclusivity and sustainability goals.